Boston Type 1 Keratoprosthesis: Visual Outcomes, Device Retention, and Complications. Issue 9 (September 2016) - Goins, Kenneth M.; Kitzmann, Anna S.; Greiner, Mark A.; Kwon, Young H.; Alward, Wallace L. M.; Ledolter, Johannes; Wagoner, Michael D.
Abstract : Purpose: To determine the visual outcomes, device retention, and complications after Boston type 1 keratoprosthesis (KPro-1) device implantation. Methods: Comprehensive review of every case of KPro-1 implantation at a tertiary eye care center. Results: The initial KPro-1 procedure, performed in 75 eyes without a previous keratoprosthesis, was included in the analysis. During the first 6 postoperative months, improvement occurred in the mean preoperative best-corrected visual acuity of 20/1265 to a mean best-obtained postoperative visual acuity of 20/97 ( P < 0.001). After a mean follow-up period of 41.4 months (range, 0.8–82.8 months), the final mean best-corrected visual acuity was 20/428. Improved vision was recorded in 43 eyes (57.3%), ambulatory vision (≥20/400) in 47 eyes (62.7%), intermediate functional vision (≥20/80) in 23 eyes (30.7%), and full functional vision (≥20/40) in 11 eyes (14.7%). The initial device was retained in 64 eyes (85.3%), with a Kaplan–Meier retention probability of 96% at 6 months and 82% at 5 years. One or more sight-threatening complications occurred in 51 eyes (68%). These included device extrusion in 11 eyes (14.7%), ulcerative keratitis in 12 eyes (16%), endophthalmitis in 7 eyes (9.3%), sterile vitritis in 3 eyes (4%), retroprosthetic membranes in 25 eyes (33.3%), maculopathy in 26 eyes (34.7%), retinal detachment in 9 eyes (12%), and progressive optic neuropathy in 7 eyes (9.3%). Conclusions: Boston KPro-1 implantation is associated with satisfactory visual outcomes and excellent device retention in a majority of cases. However, serious postoperative complications are common and may compromise the final visual result. Abstract : Supplemental Digital Content is Available in the Text.